Into the wild: coupling otolith and archival tag records to test assumptions underpinning otolith chemistry applications in wild fish - Hüssy, Karin; Haase, Stefanie; Mion, Monica; Hilvarsson, Annelie; Radtke, Krzysztof; Thomsen, Tonny B.; Krüger-Johnsen, Maria; Casini, Michele; Sturrock, Anna M. (Frontiers in Marine Science, 2024)
Chronological records of elemental concentrations in fish otoliths are a widely used tool to infer the environmental conditions experienced by individual fish. To interpret elemental signals within the otolith, it is important to understand how both external and internal factors impact ion uptake, transport and incorporation. In this study, we have combined chronological records from otoliths and archival data storage tags to quantify the influence of internal (sex, size, age, growth) and external (temperature, depth, salinity) conditions on otolith elemental chemistry of cod (Gadus morhua) in natural settings of the Baltic Sea. This study focused on elements primarily under physiological control: Phosphorus (P), magnesium (Mg) and zinc (Zn); and elements under environmental control: Strontium (Sr), barium (Ba) and manganese (Mn). Based on known spatial and temporal patterns in environmental conditions and fish size, growth, and maturity, we posed a series of hypotheses of expected otolith element patterns. Partial effects of internal and external drivers on element concentration were analyzed using a Linear Mixed Model approach with random variables (fish and year). Predicted effects of otolith concentrations of all elements under physiological control (P, Mg, Zn) showed similar trends, with distinct seasonal patterns (lowest concentration in late spring, highest concentrations in winter), and a positive correlation with water temperature, in addition to higher Zn and lower P in spawning individuals. Predicted effects of otolith concentrations of elements expected to be predominantly under environmental control showed the predicted geographic and depth-related trends based on ambient salinity (Ba) and coastal hypoxia (Mn). However, contrary to expectation, Sr was unrelated to salinity. Predicted otolith Ba, Sr and Mn concentrations also exhibited pronounced seasonal patterns that were out of phase with each other but appeared to be partly explained by spawning/feeding migrations. While performing laboratory validation studies for adult fish is typically not possible, these results highlight the importance of assessing local water chemistry and freshwater endmembers in one's study system before otolith elemental chemistry can be reliably used to reconstruct fish habitat use and environmental histories.